Uma arquitetura de software baseada em serviços para sinalização digital interativa - Freitas, Douglas Oliveira de (2013)
The use of large displays for digital signage in collective spaces is increasing for numerous purposes. For most signalling scenarios, the dynamic adjustment of the display contents is desirable. Contextual information related to the site and to the signalling profile of observers may be taken into consideration for the selection of content and for user interaction. Interactions can occur implicitly and transparently, by just mutually identifying users and systems for the selection of the content displayed, or by allowing the explicit data exchange between users and the signalling system. Mobile computing devices and wireless technologies extend the possibilities of interaction with users, creating a complex scenario for the exhibition of public and private data. The dynamic analysis of contextual information, the retrieval and generation of presentation data, and the interaction with users all require significant processing which demonstrate the complexity of encoding a digital signage system. This thesis presents a distributed system and service-based software architecture developed for creating interactive digital signage systems. The architecture allows the centralized, but scalable, creation and management of digital signage systems containing different displays and users. An implementation of the proposed architectural model and software was carried out and the results show its ability to serve the creation of dynamic, flexible and interactive digital signage systems.